SPLIMBo – Developing and Evaluating a Software Product Line for Cross-Platform IM Bots - Sarinho, Victor Travassos (Journal on Advances in Theoretical and Applied Informatics, 2017)
Instant Messaging – IM platforms spread the communication instant among their users in a fast, low cost and multimedia way. This paper presents the development and evaluation process of SPLIMBo, an open source Software Product Line that allows the production of cross-platform IM bots in a "write once, run anywhere" perspective. It is based on a Product Line Architecture that provides adapters to interact with distinct IM platforms, bot sessions defined by IM feature configurations, and a relational data bus able to integrate IM data from deployed adapters and bot sessions. As evaluation process, the LibrasZap IM game development based on SPLIMBo was described, and a comparative analysis with available bot builders was performed. They confirmed the SPLIMBo ability to build local and configurable bots being available for multiple IM platforms.